Perception and knowledge of immunization among public in Hospital Tengku Ampuan Afzan, Kuantan - Bakri, Mohamad Qardawi; Mokhtar, Faris Iskandar; Abdul Halim, Nuraini Shuhada (2017)
The world is now treated with the group of anti-vaccine or some people who refuse the application of immunization in the life. The function of immunization is to prepare human body against potential pathogens that are harmful to body system. In the recent years, there are some people who are refusing to get vaccination. Hence, this study is conducted to survey public perception and knowledge on immunization in Hospital Tengku Ampuan Afzan, Kuantan (HTAA). A validated questionnaire was used as tools to collect the data and they were processed then analysed. This survey was conducted in the area of Hospital Tengku Ampuan Afzan,Kuantan (HTAA) include of visitors and staffs around the hospital. Participants were given the questionnaire randomly without bias. The objective of this study is to investigate the relationship of participants’ education level, live area, religions to their perception and knowledge of immunization. From the 120 questionnaires distributed, we managed to get all them answered and on statistical analysis results were obtained in table and graph using SPSS system version 2.0. The results showed public have good perception and awareness of immunization. Thus, public have medium knowledge of immunization. Demographic (educational level) is influence the knowledge of immunization for this study. Hopefully this study could improve the percentage of knowledge of immunization and can used as benchmarks to provide community knowledge as well to increase promotion in the community about the immunization.